Regulation of the sale of buildings and real estate units under construction, protection of purchasers’ rights, and ensuring that real estate developers fulfill their obligations in Palestine: Comparative analytical study - Yaser Mahmoud Mohammad Zbeidat; Baraa Mohammad Ali Jamous (International Journal of Law Research and Studies, 2026)
The contract for the sale of buildings under construction is considered a relatively modern type of contract that has increasingly spread in the Palestinian real estate market, due to the growing demand for residential apartments and commercial buildings, as well as the tendency of investors and developers to sell units prior to the completion of their construction in order to obtain the necessary financing to complete the project. However, this type of sale raises significant legal issues related to the guarantees afforded to the purchaser, particularly in light of the absence of specific legislation regulating such transactions in Palestine, especially since, according to the general rules of the Majalla of Legal Provisions applicable in Palestine, the sale of a non-existent object is deemed void. Therefore, this study aims to clarify the extent to which this contract can be considered a sale, to identify the guarantees granted to the purchaser under the legislation in force in Palestine, to reveal the shortcomings therein and compare them with certain legislations that have regulated this type of contract, and finally to present a legislative perspective to address this legal gap.
Keywords: Contract for the Sale of Buildings Under Construction; off-Plan Sale; Purchaser Guarantees